Complying the LVRT grid code requirement of a fixed speed wind energy system using unified voltage and pitch angle control strategy. Issue 6 (December 2022) - Naik, Kanasottu Anil; Gupta, Chandra Prakash; Fernandez, Eugene
This paper proposes a Unified Voltage and Pitch angle Control (UVPC) strategy for fixed speed wind farm. The focus put on guaranteeing the LVRT grid code requirement when the wind farm subjected to severe faults. The UVPC consist of static synchronous compensator (STATCOM) voltage control loops with adequate pitch angle control loops which are coordinated to enhance the low-voltage ride-through capability of the wind generators thereby, complying the low voltage ride through (LVRT) grid code requirement as desired by the Germany grid code. Different scenarios such as system without STATCOM and pitch-angle controller, with STATCOM only, and system with STATCOM and pitch-angle control (i.e. UVPC) are simulated. The simulation results show that the adoption of STATCOM and pitch angle controller fulfilling the LVRT grid code requirement to ensure the continuous operation of wind turbines. Furthermore, a concept of critical clearing time (CCT) is discussed and its utility has been emphasized. Calculations, simulations and measurements provide how the increased STATCOM rating can offer an enhanced stability margin.